Load Calculation of the Load-carrying Structure of a Tank Car in Oper-ating Modes (Academic journal Industrial Machine Building Civil Engineering, 2021)
The article determines dynamic load and strength of the load-carrying structure of a tank car with elastic-friction connections in the boiler bearings and between boiler bearings and the boiler bearer. It was established that the use of elastic-friction connections allows to reduce the dynamic load on the tank car by almost 36% in comparison with the prototype. The results of stress calculation showed that the maximum equivalent stresses in the load-carrying structure of a tank car occur in the interaction area of the center sill with the draw-bar and do not exceed the allowable values. The conducted research will allow to increase the operational efficiency of tank cars by reduction of operating costs, and will also promote the creation of their innovative designs.
Keywords: transport mechanics; tank car; load-carrying structure; dynamic load; strength; fatigue strength coefficient